Risk of End-Stage Renal Disease in Psoriatic Patients: Real-World Data from a Nationwide Population-Based Cohort Study - Lee, Eun; Han, Ju Hee; Bang, Chul Hwan; Yoo, Seung Ah; Han, Kyung Do; Kim, Ha-Na; Park, Young Min; Lee, Jun Young; Lee, Ji Hyun (Scientific reports, 2019)
Psoriasis is a chronic inflammatory skin disorder mediated by the T-cell–related immune response. Psoriatic patients may have a variety of comorbidities, but their risk of end-stage renal disease (ESRD), particularly according to the subtype of psoriasis, is unclear. We investigated the risk of ESRD in patients with psoriasis according to the subtype of psoriasis and history of systemic therapy for psoriasis. A total of 2,121,228 adults (1,590,921 in the control group and 530,307 in the psoriasis group) were enrolled in this nationwide population-based cohort study until 2015. During follow-up, 1,434 of the subjects in the psoriasis group developed ESRD. After adjusting for confounding factors, psoriasis was associated with the risk of ESRD (hazard ratio (HR) 1.58, 95% confidence interval [95% CI] 1.47–1.68). The psoriatic arthritis group (HR 7.60, 95% CI 1.90–30.41) had a higher risk of ESRD than the control group. Interestingly, no such association was detected in the systemically treated group (HR 1.07, 95% CI 0.80–1.41). Moreover, the acitretin-treated group had a lower risk of ESRD (HR 0.658, 95% CI, 0.494–0.875) than the non-systemically treated group. In conclusion, the risk of developing ESRD in patients with psoriasis differed according to the type of treatment and the presence of arthritis.